WOULD SOMATOSTATIN ANALOGUE OBVIATES THE NEED OF RADICAL SURGERY IN MIDDLE EAR NET? - L, Deviga; BS, Goh; AS, Nordashima; K, Nor Azmi; S, Norlela (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Neuroendocrine tumour (NET) involving the middle ear as a primary site is exceptionally rare. To date there have been 54 reported cases in the literature. Surgical removal continues to be the mainstay of treatment however it carries with it considerable risk of complications. RESULTS We describe a 25-year-old man who presented with recurrent acute otitis media with mastoiditis of the right ear which was associated with a year history of otalgia, hearing loss and aural fullness. Otoscopic examination revealed inflamed and swollen tympanic membrane. Pure tone audiometry showed mild conductive hearing loss on the right ear while high resolution computed tomography of the temporal bone showed soft tissue opacification of middle ear and mastoid air cells without erosions of ossicles. He underwent right cortical mastoidectomy due to persistent symptoms. Intraoperatively there was granulation tissue within the right mastoid and middle ear cavity. Histopathological examination showed features consistent with a Grade 1 trabecular carcinoid tumour and absence of malignant features. It stained positive for synaptophysin and CD56 but were negative for S-100 and Chromogranin A. Ki-67 proliferation index was low (2-3%). Patient did not have symptoms of carcinoid syndrome and both the 24 hour urinary 5-hydroxylindoleacetic acid and Chromogranin A were within normal range. FDG-Positron Emission Tomography and Galium-68 DOTATE scan showed high uptake at the right mastoid and middle ear with minimal uptake in the mediastinal and paratracheal nodes. In view of the low-grade nature of the NET, monthly 20 mg Octreotide LAR was chosen as a form of treatment over that of radical surgery. Following 6 months of therapy with Octreotide LAR, the patient will be subjected to a repeat Galium-68 DOTATE scan. CONCLUSION In cases of low to intermediate grade NET involving the middle ear a combination of limited surgery and somatostatin analogue would be the treatment of choice.